Pengaruh Permainan Kartu Kuartet terhadap Pengetahuan tentang Sayur dan Buah pada Siswa Sekolah Dasar - Dita Ika Nurfila; Septriana; Endri Yuliati (Yayasan Literasi Sains Indonesia, 2022)
An Individual Food Consumption Survey 2014 showed that average of fruit and vegetable consumption of children aged 5-12 years in Central Java Province was still low. On the other hand, fruit and vegetable consumption is important to prevent overweight and obesity. One of the factors influencing low fruit and vegetable consumption in children was the lack of nutritional knowledge. Therefore it was necessary to increase knowledge by engaging attractive health education such as through quarted card games. This study was aimed to assess the effect of quartet card game on primary school students knowledgeregarding fruit and vegetable. This quasy experimental study used One-Group with Pretest-Posttest Design, conducted at SDN 02 Bejen, Karanganyar, Central Java in August 2019. The respondent were 55 students grade V. The health education wasdelivered using the quartet card game. Knowledge at pre and post-test was measured using same questionnaire then analyzed using Wilcoxon test. Median of knowledge for pretest was 70 (53-86) while for posttest 73 (46-90). This increase was statistically significant (p=0,006). It can concluded that health education using quartet card game can increase knowledge of primary school student regarding fruit and vegetable.